Pathogenetic Approach to Early Preeclampsia and the Feasibility of Pregnancy Prolongation - L. D. Belotserkovtseva; L. V. Kovalenko; V. V. Pankratov; V. N. Zinin (Общая реаниматология)
Aim. To evaluate the efficacy of cascade plasma filtration (CPF) for the correction of lipid profile and biochemical markers (sFlt-1, PIGF, sFlt-1/PIGF) in pregnant women with early preeclampsia.   Materials and Methods. A prospective controlled study of 23 CPF procedures was conducted in 11 pregnant women with early preeclampsia at gestational ages 22 to 31 weeks. The evolution of clinical manifestations of preeclampsia (BP, urine output, and proteinuria), laboratory biochemical parameters (protein/creatinine ratio, lipid profile), blood coagulation tests, and thromboelastometry (ROTEM) were assessed. In addition, the effect of CPF on the level of preeclampsia markers (sFlt-1, PIGF, sFlt-1/PIGF-ratio) as predictors of endothelial aggression was analyzed. The efficacy of extracorporeal therapy was evaluated based on the duration of pregnancy prolongation.   Results. The use of CPF as an adjunct for the treatment of early preeclampsia had a positive effect on the lipid profile by reducing cholesterol and LDL, which helped to decrease atherogenic aggression on the vascular endothelium. In addition, the extracorporeal therapy promoted reduction of the anti-angiogenic effect of sFlt-1, which was confirmed by a significant decrease in the sFlt-1/PIGF ratio from 515 [347; 750] to 378 [285; 557] (P = 0.013). The period of prolongation of pregnancy was longer in the main group (with CPF) and was 19 [5; 26] days, whereas in the comparison group (without CPF) it was 3 [1; 4] days (P < 0.001). All newborns were discharged from the hospital in a stable condition. The paper is supplemented with a clinical observation of the effective use of CPF in early preeclampsia.   Conclusion. The use of cascade plasma filtration in the treatment of early preeclampsia to prolong pregnancy could be a promising approach.